2018
DOI: 10.1002/app.47038
|View full text |Cite
|
Sign up to set email alerts
|

A rheometry method to assess the evaporation‐induced mechanical strength development of polymer solutions used for membrane applications

Abstract: Rotational and oscillatory shear rheometry were used to quantify the flow behavior under minimal and significant solvent evaporation conditions for polymer solutions used to fabricate isoporous asymmetric membranes by the self-assembly and non-solvent induced phase separation (SNIPS) method. Three different A-B-C triblock terpolymer chemistries of similar molar mass were evaluated: polyisoprene-b-polystyrene-b-poly(4-vinylpyridine) (ISV); polyisoprene-b-polystyrene-b-poly(N,N-dimethylacrylamide) (ISD); and pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Finally, the polymer precipitates to produce the final nanoporous membrane. The stabilized and frozen copolymer micelles produced by the dry/wet phase separation method is the key step of SNIPS which is the direct result of the selective layer of uniform pores via self-assembly upon solvent evaporation [60,148]. In particular, several critical strategies of membrane fabrication by SNIPS are identified: the careful adjustment of the solvent quality to prepare an appropriate self-assembly pattern [149], the introduction of metal ions to form metal-polymer complexation [150,151], the addition of low-quality solvent to stabilize the micelle core blocks in the casting solution [152], as well as the addition of volatile components to create a short solvent evaporation window before NIPS [148,152].…”
Section: Methods Of Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the polymer precipitates to produce the final nanoporous membrane. The stabilized and frozen copolymer micelles produced by the dry/wet phase separation method is the key step of SNIPS which is the direct result of the selective layer of uniform pores via self-assembly upon solvent evaporation [60,148]. In particular, several critical strategies of membrane fabrication by SNIPS are identified: the careful adjustment of the solvent quality to prepare an appropriate self-assembly pattern [149], the introduction of metal ions to form metal-polymer complexation [150,151], the addition of low-quality solvent to stabilize the micelle core blocks in the casting solution [152], as well as the addition of volatile components to create a short solvent evaporation window before NIPS [148,152].…”
Section: Methods Of Preparationmentioning
confidence: 99%
“…To increase the production scale of SNIPS membranes from the laboratory to a commercial production, some researchers elucidated the mechanisms of the self-assembly process and final assembled morphology [153,154,155,156]. For example, Caicedo-Casso et al [148] used three different A-B-C triblock terpolymer chemistries of similar molar mass to fabricate isoporous asymmetric membranes via SNIPS. The results showed that the formation of a viscoelastic film typical of asymmetric membranes was strongly dependent on solvent evaporation, with polyisoprene-b-polystyrene-b-poly(4-vinylpyridine) (ISV) solutions displaying the greatest solution viscosity and fastest strength development combined with the greatest strength magnitude of the evaporation-induced viscoelastic film.…”
Section: Methods Of Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the values ΔH m,D and ΔH f,D can be a factor in determining the polymer influence on the pure solvent. Equations (2) and (3) show the calculation methods of ΔH f,D and ΔH m,D, respectively. At the T f of the pure solvent, a freezing enthalpy change value of − 122 J/g was used, similar to the literature value, and at the T m of the pure solvent, an experimental enthalpy change value of 128 J/g was used.…”
Section: Results Phase Change Behavior Of Solventsmentioning
confidence: 99%
“…A single polymer chain is usually in a coil form in solution due to balanced interactions with the solvent and the polymer itself 1 . Molecular interactions with solvents and polymers have typical properties that can be applied to many industrial processes, and they play important roles in applications, such as membrane casting and formation [2][3][4][5][6] , battery separator preparation [7][8][9] , and polymer synthesis 10,11 , as well as in determining solubility parameters [12][13][14][15] . Recently, a 30 wt% polystyrene (PS) solution in dimethylformamide (DMF) was studied in an ultralow temperature region by Samitsu et al 16 .…”
mentioning
confidence: 99%